IV International Antarctic Conference «III International Polar Year 2007-2008:Results and Outlooks» - Editorial Board (Ukrainian Antarctic Journal, 2009)
The IV International Antarctic Conference (IV IAC - 2009) organized by the National Antarctic Scientific Center, Ministry of Education and Science of Ukraine, National Academy of Sciences of Ukraine, and III IPY Ukrainian Coordination Committee was held in Kyiv, May 12-14, 2009, 116 submissions were collected.